Desformylflustrabromine: A Novel Positive Allosteric Modulator for beta2 Subunit Containing Nicotinic Receptor Sub-Types - A. Pandya, Anshul (Current Pharmaceutical Design, 2016)
Nicotinic acetylcholine receptors are ligand-gated transmembrane ion channels that are present at the neuromuscular junction and in different locations in the nervous system. The different subtypes of neuronal nicotinic acetylcholine receptors that are found in the brain are thought to be involved in many neurological processes such as pain, cognitive function and depression, as well as in the pathophysiology of numerous neurological diseases and conditions. While the neurotransmitter acetylcholine is an endogenous agonist for all nicotinic receptors subtypes, many drugs that act as agonists and antagonists have also been identified or developed for these receptors. In addition, a novel class of compounds described as allosteric modulators have also been identified or developed for nicotinic acetylcholine receptors. Allosteric modulators are ligands that bind to nicotinic receptors at sites other than the orthosteric site where acetylcholine binds. One such allosteric modulator is desformylflustrabromine. Five chemical analogs along with desformylflustrabromine act as positive allosteric modulator for nAChRs that contain the beta2 subunit in their pentameric structure. Here the discovery and development, medicinal chemistry and pharmacological actions of desformylflustrabromine have been discussed. Desformylflustrabromine and its chemical analogs have the potential to develop into clinically used drugs for neurological diseases and conditions where nicotinic acetylcholine receptors are involved.
Keywords: functional effects